Association between dietary fatty acid patterns based on principal component analysis and fatty acid compositions of serum and breast milk in lactating mothers in Nanjing, China. Issue 18 (6th August 2021) - Ding, Ye; Yang, Yue; Xu, Fangping; Ye, Mei; Hu, Ping; Jiang, Wei; Li, Fang; Fu, Youjuan; Xie, Zhencheng; Zhu, Yunhua; Lu, Xiaolong; Liu, Ying; et al.
Abstract : This study aimed to comprehensively analyze dietary fatty acids (FAs) to evaluate their association with FA compositions of maternal serum and breast milk and assess their effects on mothers and infants. Abstract : This study aimed to comprehensively analyze dietary fatty acids (FAs) to evaluate their association with FA compositions of maternal serum and breast milk and assess their effects on mothers and infants. Overall, 121 healthy lactating Chinese mothers at 30–50 days of postpartum were enrolled and instructed to complete a Food Frequency Questionnaire, together with venous blood and breast milk sample collections. Dietary FA patterns were derived by principal component analysis with varimax rotation. Serum and breast milk FA compositions were detected using capillary gas chromatography and presented as relative concentrations (weight percentage of total FAs, %). Daily energy intake, absolute intake of most nutrients, and percentage of energy intake provided by these nutrients significantly varied among the different dietary FA patterns. There were significant differences in serum polyunsaturated fatty acid (PUFA) levels ( P = 0.011); in monounsaturated fatty acid and PUFA proportions in breast milk with respect to four patterns ( P = 0.002 and P = 0.026, respectively); and in n-6 PUFA, n-3 PUFA, linoleic acid, γ-linolenic acid, α-linolenic acid, and docosahexaenoic acid levels in breast milk ( P = 0.027, P = 0.007, P = 0.048, P = 0.034, P = 0.020, and P = 0.002, respectively). Furthermore, maternal weight retention and length-for-age z scores, weight-for-age z scores and head circumference-for-age z scores of infants with respect to the four patterns exhibited significant differences ( P = 0.038, P = 0.030, P = 0.034, and P <0.001, respectively). The results demonstrated the effect of dietary FA patterns on FA compositions of serum and breast milk, and patterns mainly characterized by LC-PUFA may have potentially beneficial effects on maternal postpartum recovery and infant growth.